PERMBERDAYAAN MASYARAKAT MANTAN WARGA BINAAN LAPAS KELAS IIB CIAMIS MELALUI INOVASI KEMASAN MODERN DAN PEMASARAN KANAL DIGITAL PRODUK OLAHAN BAYAM - Prawiranegara, Benny; Budiaman, Hendi; Maulana, Haisyam; Permatasari, Intan Nur; Djulpiqri, Fauzan (Jurnal Abdi Insani, 2025)
This community service program was carried out to strengthen the economic independence of former inmates from the Ciamis Class IIB Correctional Facility by developing small businesses based on spinach-processed products. The program emphasized two main aspects: improving packaging quality with modern and marketable designs, and enhancing marketing strategies through digital platforms. The mentoring process was conducted gradually, starting with technical training in product processing, hands-on practice in designing hygienic and attractive packaging, and the application of promotional strategies using social media and online marketplaces. The outcomes revealed noticeable improvements in participants’ capacity to manage small businesses, particularly in producing market-ready packaging and promoting products through digital channels to reach wider consumers. Beyond the economic benefits, the program also fostered greater self-confidence, independence, and contributed to the social reintegration process of former inmates into the community.